Endovascular salvage of an immature radiocephalic arteriovenous fistula: a case report - Limanto, Danang Himawan; Jatiman, Thomas; Juliana (Journal of Indonesia Vascular Access, 2025)
Background: Autogenous arteriovenous fistulas (AVFs) are the preferred vascular access for hemodialysis, offering superior patency and lower complication rates compared to grafts or catheters. However, non-maturation occurs in 20–40% of cases, often due to juxta-anastomotic stenosis or accessory venous runoff, leading to prolonged catheter dependence and increased morbidity. Endovascular salvage strategies such as balloon-assisted maturation (BAM) and coil embolization achieve technical success rates exceeding 90% and are now central to access preservation. Case Presentation: We report a 66-year-old male with stage V chronic kidney disease on regular hemodialysis who developed an immature left radiocephalic AVF four months post-creation, complicated by ipsilateral hand edema. Duplex ultrasonography revealed draining vein diameters of 0.42–0.54 cm and flow volumes of 130–150 mL/min. Venography confirmed juxta-anastomotic stenosis with competitive runoff into the distal cephalic vein. The patient underwent endovascular salvage consisting of coil embolization of the cephalic runoff and balloon angioplasty of the draining vein using sequential 4.0 and 6.0 mm balloons. Post-procedural venography demonstrated elimination of distal runoff and restoration of antebrachial flow. Clinically, hand edema regressed, and AVF patency was preserved. Conclusion: Combined coil embolization and angioplasty can successfully salvage immature AVFs with venous stenosis and accessory runoff. This case underscores the importance of structured duplex surveillance, early identification of failing maturation, and timely endovascular intervention to preserve autogenous vascular access.